Mg/Ca ratios in benthic foraminifera from surface sediments - Rodrigo Sebastian Martín; Paula Belén Albarracín; Natalia Luz García Chapori; Cecilia Laprida; Jeroen Groeneveld; Sabine Kasten (PANGAEA, 2023)
Today, climate change has become an issue of global significance. These changes are known to be deeply related to heat distribution and paleoceanographic variations. On the other hand, it is clear that the chemistry of benthic foraminifera shells is an irreplaceable tool to understand these changes at great depths. In this work, the differences between the magnesium assimilation in Uvigerina sp. and Cibicides wuellerstorfi. Mg/ca records from shells can be used for paleothermometry reconstruction of deep ocean currents. But it is necessary to control the impact that the carbonate ion could have on the benthic foraminiferal fauna. Here, a database containing the records of Magnesium/Calcium present in the benthic foraminifera of the western South Atlantic between 32.69°S and 47.3°S were analyzed. The study was carried out on the species of the genus Uvigerina spp. and in Cibicidoides wuellerstorfi. For sediment cores GeoB2715-1, GeoB2718-2, GeoB2727-1, GeoB6208-1, GeoB6222-2, GeoB6309-2, GeoB6330-1, GeoB6334-2 and GeoB6336-2 we used the ages originally published in Raitzsch et al. (2008, doi:10.1594/PANGAEA.759564). And for cores GeoB22702-1, GeoB22703-1, GeoB22704-1, GeoB22706-1, GeoB22707-2 -53,78333, GeoB22708-3, GeoB22712-3, GeoB22715-1, GeoB22721-1, GeoB22723-2, GeoB22725-1, GeoB22735-2, GeoB2703-6, GeoB2722-1, GeoB6212-2, GeoB6213-1, GeoB6334-1, LBV T1-2, LBV T4-1, LBV T6-1, LBV T12-1, LBV T13-2, LBV T406-2 and LBV T407-2 we used the ages originally published in García Chapori et al. (2019, doi:10.1594/PANGAEA.907931). Mg/Ca measurements were performed with inductively coupled plasma optical emission spectrometry (ICP-OES; Agilent Technologies, 700 series with ASX-520 Cetac autosampler and micronebulizer) at MARUM, University of Bremen.